Retail Marketing of Menthol Cigarettes in Los Angeles, California: a Challenge to Health Equity - Smiley, Sabrina L. (Prev Chronic Dis, 2021)
INTRODUCTION: Sales of menthol cigarettes continue to increase, accounting for a third of the US cigarette market. Retail marketing of menthol cigarettes is a contributing factor to tobacco-related health disparities. To inform regulation to address associated disparities, we examined retail marketing strategies for menthol cigarettes and their features and characteristics in relation to neighborhood racial/ethnic composition. METHODS: We used multilevel regression models to examine associations of neighborhood racial/ethnic composition and store type with menthol cigarette sales outcomes, including availability, exterior advertising, price promotions, and price in a sample of tobacco retailers (N = 673) in Los Angeles County neighborhoods with a median or below-median household income. We also recorded the prices of Newport cigarettes (the highest selling menthol cigarette brand in the United States) and blu disposable menthol e-cigarettes. RESULTS: Overall, 94.5% of retailers sold menthol cigarettes, 31.2% displayed menthol cigarette price promotions, and 30.2% displayed at least one menthol cigarette advertisement on their exterior. Adjusting for racial/ethnic zip code cluster and store type, stores located in predominantly African American neighborhoods showed significantly higher odds in the availability of Newport cigarettes than stores in Hispanic neighborhoods (OR = 0.21; 95% CI, 0.09–0.53; P = .001) or non-Hispanic White (OR = 0.12; 95% CI, 0.05–0.31; P < .001) neighborhoods. Stores located in predominantly African American neighborhoods displayed significantly higher odds of having price promotions for menthol cigarettes and storefront advertisements than those in Hispanic neighborhoods (OR = 0.51; 95% CI, 0.30–0.88; P = .02 and OR = 0.25; 95% CI, 0.13–0.48; P < .001, respectively). CONCLUSION: In 2016 and 2017, menthol cigarettes were widely available in Los Angeles County across racial/ethnic neighborhoods. We found a disproportionate number of storefront advertisements and price promotions for menthol cigarettes in stores located in predominantly African American neighborhoods along with the lowest advertised pack price. This evidence supports tobacco control policies that restrict menthol cigarette sales in the retail environment.